2019
DOI: 10.1590/1678-5150-pvb-6122
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and pathological aspects of bovine lymphoma affecting the spinal cord

Abstract: Clinical and pathological features of bovine lymphoma involving the spinal cord were evaluated through a retrospective study of the necropsy database from 2005 to 2017. Thirty-four cases of bovine lymphoma were found, 24 of which had central nervous system involvement restricted to the spinal cord. All cattle were Holstein cows 2.5-12 years-old (median age, six years-old). The clinical course was 7-21 days, and the main neurological sign was pelvic limb paresis (81.8%). The lymphoma often affected the spinal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 44 publications
1
2
0
Order By: Relevance
“…Although our findings were sometimes difficult to interpret, these results confirm the evidence for the multicentric distribution of EBL in adult cattle [18]. To our knowledge, the current study is the first to report the description of microstructural changes involving lymph node trabeculae and myocardial fibres from leukemic cows.…”
Section: Fig 4 Diffuse Lesions In the Liver Of The Cowssupporting
confidence: 80%
“…Although our findings were sometimes difficult to interpret, these results confirm the evidence for the multicentric distribution of EBL in adult cattle [18]. To our knowledge, the current study is the first to report the description of microstructural changes involving lymph node trabeculae and myocardial fibres from leukemic cows.…”
Section: Fig 4 Diffuse Lesions In the Liver Of The Cowssupporting
confidence: 80%
“…The clinical signs are variable and unspecific, such as body weight loss, inappetence, pallor, weakness, and decrease in milk production (2). However, specific clinical syndromes may also develop according to the site affected by the lesions, including enlargement of peripheral and visceral lymph nodes, tachypnea, stertorous respiration, dyspnea, subcutaneous edema, dysphagia, diarrhea, indigestion, tympanums, congestive heart failure, decubitus, hindlimb lameness, and paraplegia (4,5,8). Although the time between the onset of clinical signs and death varies (5), most cases tend to have subacute to chronic course (2).…”
Section: Histological Descriptionmentioning
confidence: 99%
“…The recent veterinary literature on tumors of domestic animals follows the Revised European-American Classification of Lymphoid Neoplasms (REAL), provided by the World Health Organization, which identifies each subtype of (8). The application of this classification scheme in some studies indicated that the majority of EBL are diffuse large B-cell lymphoma (4,5,9).…”
Section: Histological Descriptionmentioning
confidence: 99%